The role of informal street activities in the context of conserving urban cultural entity : case study : Malioboro Street, Yogyakarta Indonesia - Sholihah, Arif Budi (2005)
As an important element of urban form, street functions as social space, commercial space, cultural space, as well as channels of movement and symbolic representation of local tradition and culture. Since street spaces comprise not only physical element but also the people who are moving, using, acting, and dancing within and around them, informal street activities emerge as an integral part of street life. This characteristic is endemic to most urban streets in South-east Asia and Malioboro Street in Yogyakarta, Indonesia, is without exception one of these streets. The aim of this study is to demonstrate the significant role of informal street activities (street culture) as an integral part of urban culture and image and to provide guidelines to conserve these significant attributes in enhancing the richness and the complexity of Malioboro Street as the main commercial-historic-cultural corridor in the historic city of Yogyakarta. The study focuses on the contextual relationship and interaction between people and the built environment, to emphasise this significant ambience and the role of informal street activities in the current urban design approach. The study intend to prove that informal street activities have a significant role on enhancing diversity in the use of street, activating public life and increasing attractiveness. Despite these positive attributes, these informal activities are seen to be one major obstacle in the process of managing urban spaces by the local authorities because of the inherent issues of conflicting occupation of public urban spaces that result in the hindering of pedestrian and vehicular movements, decreasing sidewalks space and more often, general cleanliness of the urban environment. Urban design solutions are formulated to exploit all possibilities to conserve the informal street activities as significant attributes in enhancing the richness and the complexity of the street and at the same time try to resolve the problems that arose in managing the conflicts and issues pertaining to these activities and the spaces they occupied.